Low antibody titers five years after vaccination with the CYD-TDV dengue vaccine in both pre-immune and naïve vaccinees - Velumani, Sumathy (2016)
Globally, dengue virus (DENV) is one of the most widespread vector-borne viruses. Dengue disease affects populations in endemic areas and, increasingly, tourists who travel to these countries, but there is currently no approved vaccine for dengue. A phase 3 efficacy trial with Sanofi-Pasteur's recombinant, live-attenuated, tetravalent dengue vaccine (CYD-TDV) conducted in South East Asia showed an overall efficacy of 56% against virologically confirmed dengue infections of any severity and any of the four serotypes, but the long-term protection of the vaccine has yet to be demonstrated. To address longevity of antibody titers and B cell memory, we recalled study participants from an earlier CYD immunogenicity study (Phase 2) conducted in Singapore that enrolled healthy volunteers in the year 2009. Depending on the age group, 57–84% of the participants initially generated a neutralizing antibody titer ≥ 10 to all four DENV serotypes 28 days after the third and final dose. We observed very low antibody titers in blood samples collected from 23 vaccinees five years after the first dose, particularly titers of antibodies binding to virus particles compared with those to recombinant E protein. The in vivo efficacy of plasma antibodies against DENV-2 challenge was also tested in a mouse model, which found that only 2 out of 23 samples were able to reduce viremia. Although the sample size is too small for general conclusions, dengue immune memory after vaccination with CYD-TDV appears relatively low.